Postmortem Stability of Ebola Virus - Joseph B. Prescott; Trenton Bushmaker; Robert J. Fischer; Kerri Miazgowicz; Seth D. Judson; Vincent J. Munster (Emerging Infectious Diseases, 2015)
The ongoing Ebola virus outbreak in West Africa has highlighted questions regarding stability of the virus and detection of RNA from corpses. We used Ebola virus–infected macaques to model humans who died of Ebola virus disease. Viable virus was isolated <7 days posteuthanasia; viral RNA was detectable for 10 weeks.